أثر معالجة سطح الوتد الليفي ببيروكسيد الهيدروجين في شدة ارتباطه مع الكومبوزيت (دراسة مخبرية) - خير, أروى; حسين, علي (Latakia University Journal -Medical Sciences Series, 2017)
خلفية البحث وهدفه : يعتبر الارتباط بين الكومبوزيت والأوتاد الليفية ضعيفاً عند مقارنته بارتباط الكومبوزيت مع النسج السنية.يهدف البحث الى تقويم اثر بيروكسيد الهيدروجين كمحل للسطوح في زيادة قوة الارتباط بين الوتد الليفي و قلب الكومبوزيت .المواد والطرائق : تم تحضير 45 قطعة وتد ليفي كوارتز و 45 قطعة وتد ليفي زجاجي .تمّ تقسيم النماذج في كل مجموعة ل3 مجموعات فرعية وهي : معالجة بالسايلن فقط كمجموعة شاهدة ، و المعالجة ببيروكسيد الهيدروجين 20% لمدة 10 دقائق ،و 10% لمدة 20 دقيقة . تمّبناء قلوب الكومبوزيت وقياس قوى القص للأوتاد بوساطة جهاز الاختبارات الميكانيكي وتم تحليل النتائج إحصائياً .النتائج : تفوق بيروكسيد الهيدروجين على المعالجة بالسايلن فقط في مجموعة أوتاد الكوارتز فقط، ولم تظهر المعالجة ببيروكسيد الهيدروجين فروق دالة بين الأوتاد الزجاجية والكوارتز.الاستنتاجات :بيروكسيد الهيدروجين حسن من الارتباط بين الوتد الكوارتز والكومبوزيت ، بينما فشل في تحسين ارتباط الأوتاد الزجاجية مع الكومبوزيت.Background and Aim : Retention between composite and fiber post is still below the acceptable level when compared with the retention between composite and dental structure. This study aimed to evaluate the effect of H2O2 as a chemical solution to improve the mechanical connection between fiber post and composite core.Materials and Methods:45 glass fiber posts and 45 quartz fiber posts were prepared. The specimens were randomly distributed into 3 subgroups, including application of silane (S) , etching with H2O2 10% for 20 minutes(H1) , etching with H2O2 20% for 10 minutes (H2). composite core was placed. Shear bond strength values of posts and composite resin cores were measured using a mechanical test machine (Instron). data were analyzed Statistically .Results :There were significant differences between the shear bond strength for (H1,H2) And (S) in quartz groups only (P<0.05). There was no significant difference between glass and quartz groups (P>0.05).Conclusions:The surface treatment of quartz fiber posts with H2O2 significantly enhanced the shear bond strength of the composite core. Application of H2O2 to the Glass fiber post surfaces was not effective.